High Pressure-Temperature Viscosity Study of an Indian Natural Rock - Pandey, Kamlesh; Mauli Dwivedi, Mrigank (Asian Journal of Chemistry, 2010)
Viscosity measurement of the natural rocks is an important experimental tool for the knowledge of extrusive and intrusive igneous changes inside the earth. The viscosity is measured by the falling sphere technique. The chemical composition of the rock was analyzed by the EPMA.